New San Luis Obispo Buddhist Church Building Fund Report, 1963 - San Luis Obispo Buddhist Church::::::author::: (1963)
A 1963 report listing the individuals or organizations and their pledges or their cash donations to the new San Luis Obispo Church Building Fund.